A MARKETING BOOKLET FOR THE ALANA HOTEL SURABAYA: THE BEST WAY TO EMPHASIZE THE UNIQUENESS OF ITS PRODUCTS IN PROMOTING ITSELF TO INSTITUTIONS AND COMPANIES - Lia Margaretha; Jusuf I Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
The Alana is a four-star hotel located in the South of Surabaya. It was built in 2013, which means that it is still a new hotel. Since it is new, it lacks the necessary promotion tool to reach the institutions and companies. In fact, The Alana does not have the promotion tool which emphasizes its excellence and uniqueness of the products. To solve the problem, The Alana  needs  a  marketing  booklet,  which  can  help  them  to  show  their  strengths.  This marketing  booklet  consists  of  table of  contents, company overview  (about  The  Alana), product descriptions (hotel  rooms, room types, hotel facilities, and meeting rooms), and contact information (contact  us). By having this information, a marketing booklet will become the best tool for The Alana to show the strengths of their products and help them to reach their target market